1999
DOI: 10.1021/ja9827090
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of 2-Azido-1-methylimidazole in Aqueous Solutions. Observation of the 1-Methyl-2-imidazolylnitrenium Ion

Abstract: Irradiation of 2-azido-1-methylimidazole (12) in aqueous solution gives products from two reaction channels. One pathway involves a ring opening typical of azidoheterocycles. The observed products are glyoxal bis-hydrate, the methylammonium ion, and cyanamide; a glyoxal bis-oxime is presumed to be the intermediate initially formed in the ring opening. The other pathway leads to products that retain the five-membered ring, the 2-amino-4,5-dihydro-4,5-dihydroxy-1-methylimidazolium ion 3, its monophosphate ester … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 57 publications
3
19
0
Order By: Relevance
“…McClelland and coworkers examined the hydrolysis of 94. [141][142][143][144] The hydrolysis mechanism of Scheme 4.28 is consistent with kinetic data. 141,142 An intermediate that can be trapped by H 2 O, 142 phosphate, 143 or glutathione (GSH) 139,142 was identified as the nitrenium ion 95.…”
Section: Heterocyclic Nitrenium Ionssupporting
confidence: 80%
See 1 more Smart Citation
“…McClelland and coworkers examined the hydrolysis of 94. [141][142][143][144] The hydrolysis mechanism of Scheme 4.28 is consistent with kinetic data. 141,142 An intermediate that can be trapped by H 2 O, 142 phosphate, 143 or glutathione (GSH) 139,142 was identified as the nitrenium ion 95.…”
Section: Heterocyclic Nitrenium Ionssupporting
confidence: 80%
“…produced by protonation of nitrene 96a generated by LFP of azide 97a. 144 The rate constants k s and k gs-were determined to be 9.4 s À1 and 3 Â 10 7 M À1 s À1 , respectively. 144 The ion 95a has a lifetime of over 100 ms at neutral pH in the absence of buffers or other nucleophiles.…”
Section: Heterocyclic Nitrenium Ionsmentioning
confidence: 99%
“…[2] Among these compounds, 3 does not isomerize, [3] and it undergoes photochemical ring cleavage [4] that provides a facile route to small molecules such as heterodienes, which are useful buildingblocks in hetero-Diels-Alder reactions. [5] These studies indicated that the azido-tetrazole equilibrium is normally affected by the solvent and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In light of these results, we would expected that the photochemical reactivity of azido-tetrazole mixtures 1 and 2 does not differ substantially from the photochemical behaviour of azide 3, even if this latter was carried out in water. [4] This study was carried out in view of the chemical, [7] biological [8] and pharmacological [9] importance of these nitrogen-linked azole systems and to find the influence on the photochemical reactivity of the cyclized or open-chain forms.…”
Section: Introductionmentioning
confidence: 99%
“…McClelland and co-workers proposed a similar ring opening for the nitrene derived from 2-azido-1-methylimidazole in aqueous solution. [9] Pozharskii and coworkers have shown that oxidation of 1,2-diaminobenzimidazole leads to the corresponding coarctate ring opening after oxidation, affording 3-amino-1,2,4-triazines through re-cyclization. [10] Proton shift at 17 to the more basic nitrogen affords intermediate 18.…”
Section: Resultsmentioning
confidence: 99%